THE INFLUENCE OF LEADERSHIP STYLE AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. CAHAYA ABADI PAINTING - Angga Juanda; Yeni Septiani; Enjah Pipit Fitriyadi (International Journal Management and Economic, 2024)
This study investigates the influence of leadership style and work motivation on employee performance at PT. Cahaya Abadi Painting. Using a quantitative research approach, data was collected from 60 employees within the company's Sample Room Department Development division. The study employed multiple linear regression analysis to assess the impact of the independent variables leadership style and work motivation on the dependent variable, employee performance. The findings indicate that while leadership style has a positive, albeit not significant, effect on employee performance, work motivation shows a strong and significant positive effect. The combined influence of leadership style and work motivation accounts for a substantial proportion of the variance in employee performance, suggesting that both factors are crucial in optimizing workforce productivity. These results are consistent with previous studies that highlight the pivotal role of motivation in enhancing employee performance. However, the limited impact of leadership style observed in this context suggests the need for further investigation into other organizational factors that may mediate or moderate this relationship.